Impacto do conceito de empacotamento de partículas na dosagem de concretos de alto desempenho - Oliveira, Caroline Oliveira E. [UNESP]; Maciel, Geraldo de Freitas [UNESP]; De Castro, Alessandra Lorenzetti; Barbosa, Mônica Pinto [UNESP]; Campos, Renan Serralvo [UNESP] (FapUNIFESP (SciELO), 2018)
High performance concrete (HPC) is a material that has specific characteristics, such as high compressive strength and high durability. In order for this concrete to meet its specific characteristics, a careful selection and dosage of its components must be carried out. Thus, this paper aims to contribute with HPC dosage study using the concept of particle packing, where the optimal proportion of particulate components was determined by Alfred model, also known as modified Andreasen model. Held the dosage of the HPC, was analyzed the influence of particle packing on its mechanical performance and on the rheological properties of the cement paste and mortar HPC constituents. The optimized HPC based on particle packing concept presented satisfactory compressive strength at 28 days, which can be classified as a high strength concrete, and superior compressive strength to the reference HPC. In the rheological characterization of cement paste and mortar, the use of packing concept caused an increase of the fluidity, facilitating the flow, without harming the stability of concrete mix.
Impact of particle packing concept on dosage of high performance concrete
Keywords: High performance concrete; Mix design; Particle packing; Rheology